Public Transport Use Among Workers in Bali: Behavioral Evidence for Green Economy-Oriented Mobility Policy - Putu Ayu Pramitha Purwanti; Ni Putu Wiwin Setyari; Ni Nyoman Reni Suasih; Vicente Manuel Luis Guterres; I Putu Herry Mahendra Putra; Ni Putu Winda Apriyani (Institute of Multidisciplinary Research and Community Service, 2026)
Public transport is a strategic instrument for reducing congestion, lowering transport-related emissions, and supporting a green economy. However, workers in Bali still rely heavily on private vehicles for commuting, even after the development of Sarbagita and Teman Bus services. This study aims to examine the socioeconomic, demographic, and employment-related factors associated with workers' decisions to use public transport in the Sarbagita area of Bali and to derive worker-oriented policy implications for sustainable mobility. A quantitative survey was conducted among workers in Denpasar, Badung, Gianyar, and Tabanan, and the data were analyzed using a probit model and marginal effects. Model diagnostics and robustness checks were also conducted using Variance Inflation Factor (VIF), Log-Likelihood, McFadden Pseudo R-squared, and re-estimation after excluding high-income observations. The probit results show that gender, income, working hours, employment status, and location significantly affect the probability of using public transport. Income, working hours, and formal employment status reduce the likelihood of using public transport, while residence in Denpasar and Badung increases it. The marginal-effect results indicate that living in better-served areas increases the probability of public transport use by 27.77 % points. In contrast, higher income, formal employment, and longer working hours decrease it. The robustness check confirms that the main findings remain stable after excluding high-income observations. These findings suggest that public transport policy in Bali should move beyond infrastructure provision by aligning service hours, accessibility, reliability, and information systems with workers' commuting patterns. Keywords: Public transport, Worker behavior, Green economy, Probit Model.